RESEARCH OF STUDENTS' SATISFACTION WITH EDUCATIONAL SERVICES IN HIGHER EDUCATION BY USING QUESTIONNAIRE - Stankov, Biljana M; Jovičić, Dragoljub; Marjanski Lazić, Sonja (International Journal of Economic Practice and Policy, 2016)
The research problem concerns the role and importance of educational services as an instrument of marketing mix in the higher education institution for management, as well as the students' satisfaction with the quality of educational services. In addition to determining their attitudes and opinions about the investigated issues, the problem of research deals with the influence of the mentioned instrument on the number of educational services users. The research subject is related to the establishment of links between marketing mix and students' satisfaction and choice of a particular higher education institution and service it is offering. The paper studied two groups of variables: the general characteristics of the students and the characteristics of educational services. The overall objective of the research is concerned with the identification of the most important groups of factors that affect students' satisfaction with the educational service and its influence on their choice of a particular higher education institution and its offered service. Additionally, this study includes determining the degree of correlation among the mentioned groups of factors. The specific objective of the research is to determine, in the context of the results, the intensity of impact each factor has on the satisfaction and choice of students in order to determine which factors exert a powerful influence and which the weakest influence on a mentioned research subject. Descriptive method will be used as the basic method for researching defined subjects, while content analysis and comparative method will be used as auxiliary methods. In the process of collecting research data the authors will apply the test method.
Keywords: higher education institution; EDUCATIONAL SERVICES; marketing mix; students satisfaction; questionnaire